Early Trypanosoma cruzi Infection Triggers mTORC1-Mediated Respiration Increase and Mitochondrial Biogenesis in Human Primary Cardiomyocytes - Libisch, M. Gabriela; Faral-Tello, Paula; Garg, Nisha J.; Radi, Rafael; Piacenza, Lucía; Robello, Carlos (Frontiers in Microbiology, 2018)
Chagasic chronic cardiomyopathy is one of the most frequent and severe manifestations of Chagas Disease, caused by the parasite Trypanosoma cruzi. The pathogenic and biochemical mechanisms responsible for cardiac lesions remain not completely understood, although it is clear that hypertrophy and subsequent heart dilatation is in part caused by the direct infection of cardiomyocytes. In this work, we evaluated the initial response of human cardiomyocytes to T. cruzi infection. Immediately after infection, cardiomyocytes dramatically change their gene expression patterns, up regulating most of the genes encoding for OXPHOS and ribosomal proteins. As a consequence, infected cells increase their oxidative metabolism and exhibit mitochondrial biogenesis. We demonstrate that these changes are mediated by mTORC1 and hence reversed by rapamycin, resembling the molecular mechanisms described for the non-chagasic hypertrophic cardiomyopathy. Our results provide new insights into the host response to parasite infection and the pathogenesis of chronic chagasic cardiopathy.